- Perancangan Sistem Inventaris Barang Berbasis Web Pada Institut Teknologi dan Bisnis (ITBis) Lembah Dempo: - - Megira, Selvy; Prakarsya, Agustian; Sari, Yusi Nurmala (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2022)
Utilization of computer technology makes processing of data and information can be done quickly and accurately. Advances in technology and information also provide many conveniences in processing inventory data. inventory of goods is the recording of data related to goods or assets that exist in the organization. Institute of Technology and Business (ITBis) Lembah Dempo has not fully implemented an information system for data, especially in inventory processing. This study aims to design an inventory information system that will be used as an effort to increase the efficiency of computerized inventory recording that can be implemented at the Institute of Technology and Business (ITBis) Lembah Dempo. In designing this inventory information system using a prototyping system development method and a database designed using an ERD (Entity Relationship Diagram).